ANALISIS JARINGAN KOMUNIKASI (SOCIAL NETWORK ANALYSIS) PROGRAM MBG INDONESIA - Fauziah, Rizky (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: The Free Nutritious Meal (MBG) program, launched in early 2025, has sparked considerable controversy and a communication crisis. Between January 6 and May 1, 2025, the program operated amid increasing complaints, including 17 reported food poisoning incidents involving 1,602 victims across 10 provinces, delays in payments to MBG’s food provider partners, and sweeping cost-efficiency. These controversies have led to a crisis of public trust, which is observable through shifts in public opinion on X. This study aims to map the communication network surrounding the MBG discourse on X in Indonesia. The investigation focuses on user activity volume, top influencers, viral posts, inter-user communication networks, and sentiment analysis. The research applies a social network analysis method using X as the data source. The findings indicate that, between May 1 and May 31, 2025, 400 active X users disseminated information about the MBG program, resulting in 498 communication networks. The data analysis suggests that government actors were largely absent in addressing the communication breakdown, which itself became a major trigger of the crisis.                               Keywords: MBG, food poisoning, efficiency, X, communication crisis, Indonesia                                 Abstrak: Program Makanan Bergizi Gratis (MBG), yang diluncurkan pada awal tahun 2025, telah memicu kontroversi dan krisis komunikasi yang cukup besar. Antara 6 Januari dan 1 Mei 2025, program ini beroperasi di tengah meningkatnya keluhan, termasuk 17 insiden keracunan makanan yang dilaporkan yang melibatkan 1.602 korban di 10 provinsi, keterlambatan pembayaran kepada mitra penyedia makanan MBG, dan efisiensi biaya yang meluas. Kontroversi ini telah menyebabkan krisis kepercayaan publik, yang dapat diamati melalui pergeseran opini publik tentang X. Studi ini bertujuan untuk memetakan jaringan komunikasi seputar wacana MBG tentang X di Indonesia. Investigasi ini berfokus pada volume aktivitas pengguna, influencer teratas, unggahan viral, jaringan komunikasi antarpengguna, dan analisis sentimen. Penelitian ini menerapkan metode analisis jaringan sosial dengan menggunakan X sebagai sumber data. Temuan menunjukkan bahwa, antara 1 Mei dan 31 Mei 2025, 400 pengguna X aktif menyebarkan informasi tentang program MBG, yang menghasilkan 498 jaringan komunikasi. Analisis data menunjukkan bahwa aktor pemerintah sebagian besar absen dalam mengatasi gangguan komunikasi, yang menjadi pemicu utama krisis. Kata kunci: MBG, keracunan makanan, efisiensi, X, krisis komunikasi, Indonesia